Cardiomyopathy in Pregnancy: A Review Literature - Ayu Asri Devi Adityawati; Anna Fuji Rahimah; Heny Martini; Cholid Tri Tjahjono (Universitas Brawijaya, 2021)
AbstractBACKGROUND: Pregnancy is an experience that many women can achieve. Pregnancy is generally well tolerated in asymptomatic patients with cardiomyopathies but in restrictive form cardiomyopathy, pregnancy cannot be tolerated because of poor prognosis. Prior cardiac events, poor functional class (New York Heart Association class III or IV), or advanced left ventricular systolic dysfunction are present, the risk of maternal cardiac complications during pregnancy are markedly increased. Worsening of the clinical condition can occur during pregnancy, despite intensive medical treatment. Although the incident of cardiovascular disease is present 0.5-4% in developed countries, our knowledge about various of cardiomyopathy and pregnancy should be updateable.CONCLUSION: Our literature provide three types of cardiomyopathy in pregnancy with an example condition for each type that relevant during pregnancy. Peripartum cardiomyopathy is the most common form of cardiomyopathy occured in pregnancy therefore a thorough review is needed to give best outcome for pregnancy. Arryhtmia is the commonnest form in hypertrophic cardiomyopathy which need to be regularly monitored and measure should be taken if the arryhtmia is life threatening for mother and the child. Cardiac amyloidosis is the common form of restrictive cardiomyopathy in pregnancy.Keywords: Pregnancy; Cardiomyopathy; Peri Partum Cardio Myopathy (PPCM), Pregnancy, Heart Failure